Collaural fistula: a case report - Subha, Sethu Thakachy; Janakiram, Trichy Narayanan; Goel, Aparajita; Susheen, H. K. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Cervico-aural [collaural fistula] fistula is rare and it accounts for less than 5% of branchial cleft anomalies. In this paper, we report one such case of a 9 year old girl who was presented to us with two discharging cutaneous openings on the right side; one in the floor of the external auditory canal and another in the neck at the junction of the upper 2/3rd and lower third of the sternomastoid muscle along its anterior border.